"I Just Kept It to Myself": The Shaping of Latina Suicidality Through Gendered Oppression, Silence, and Violence. Issue 3 (17th August 2018) - Szlyk, Hannah S.; Gulbas, Lauren; Zayas, Luis
Abstract : Suicide is a critical issue among Latina youth. In this study, we use family case analysis to explore how gendered oppression, silencing, and violence shape suicidal behaviors among a sample of Latina daughters ( n  = 10), and their parents. For comparison, we include family narratives from Latina adolescents with no histories of suicide attempts ( n  = 10). Results suggest how secrets and silence, as indicative of gendered oppression, may catalyze a suicide attempt. The risks are particularly salient when daughter and mother both have experienced violence that conflicts with gendered cultural scripts. Findings highlight the importance of parental engagement and exploration of histories of violence in the treatment of Latina suicide attempters. Future research should incorporate the risk factors of gendered oppression and violence to better understand the development of suicidality among Latina women. Abstract : El suicidio es un problema crítico entre las jóvenes latinas. En este artículo, usamos un análisis de casos familiares para averiguar cómo la opresión de género, el silenciamiento y la violencia determinan conductas suicidas entre una muestra de hijas latinas ( n  = 10) y sus padres. Para comparar, incluimos relatos familiares de adolescentes latinas sin historias de intentos de suicidio ( n  = 10). Los resultados sugieren cómo los secretos y el silencio, como indicadores de la opresión de género, pueden catalizar un intento de suicidio. Los riesgos son particularmente prominentes cuando la madre y la hija han sufrido una violencia que contradice los guiones culturales de género. Los resultados destacan la importancia de la participación de los padres y del análisis de las historias de violencia en el tratamiento de mujeres latinas que han intentado suicidarse. Las investigaciones futuras deberían incorporar los factores de riesgo de la opresión de género y de la violencia para comprender mejor el desarrollo de las tendencias suicidas entre las mujeres latinas. Abstract : 自杀是拉丁裔青少年中间一个严重问题。本文中我们使用家庭案例分析来探索性别压迫, 缄默以及暴力是如何影响由拉丁裔女孩 ( n  = 10)和其家长组成的样本中的自杀行为。为了做比较, 我们包括了从没有自杀企图历史的拉丁裔青少年收集的家庭叙述 ( n  = 10)。结果显示作为性别压迫指标的秘密和缄默可能促使自杀企图。当母亲和女儿都经历过和性别文化标准有冲突时风险格外突出。研究结果强调了家长参与和对于拉丁裔试图自杀人群治疗中暴力历史的探索。未来研究应该包括性别压迫和暴力风险因素来更好的理解这一发展。